2011
DOI: 10.1021/jp209974f
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Validation of the Structure of a Transiently Formed and Low Populated FF Domain Folding Intermediate Determined by Relaxation Dispersion NMR and CS-Rosetta

Abstract: We have recently reported the atomic resolution structure of a low populated and transiently formed on-pathway folding intermediate of the FF domain from human HYPA/FBP11 [Korzhnev, D. M.; Religa, T. L.; Banachewicz, W.; Fersht, A. R.; Kay, L.E. Science 2011, 329, 1312–1316]. The structure was determined on the basis of backbone chemical shift and bond vector orientation restraints of the invisible intermediate state measured using relaxation dispersion nuclear magnetic resonance (NMR) spectroscopy that were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 92 publications
(275 reference statements)
0
13
0
Order By: Relevance
“…Indeed, we previously showed that point substitution mutations as well as single-atom substitutions can be used to stabilize RNA ESs 8,16,17,74 . In addition, various forms of mutagenesis have successfully been used to stabilize ESs of proteins 30,33,34,75,76 . Here, it is critically important to measure a comprehensive set of RD data that probe various aspects of conformation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we previously showed that point substitution mutations as well as single-atom substitutions can be used to stabilize RNA ESs 8,16,17,74 . In addition, various forms of mutagenesis have successfully been used to stabilize ESs of proteins 30,33,34,75,76 . Here, it is critically important to measure a comprehensive set of RD data that probe various aspects of conformation.…”
Section: Discussionmentioning
confidence: 99%
“…In this manner, I becomes the dominant conformation in solution and is now "visible" using standard NMR methods. The structure of the truncated mutant was determined using classical NMR approaches and shown to be the same as that of the invisible I state elucidated as described above (38). The importance of cross-validating structures of excited states via traditional NMR studies of designed, stabilizing mutants cannot be overemphasized, especially given that the development of the RD methodology is still progressing.…”
Section: Nmr Methods For Studying Excited Biomolecular Conformationsmentioning
confidence: 99%
“…For the first three variants (FF 1-60 , FF , and FF 9-60 ), 1 H N -15 N HSQC spectra are very similar, with two sets of signals corresponding to states M and D of the protein, while only a single set of signals is observed in NMR spectra of FF 11-60 that belong to the monomeric form. We have previously determined the structure of FF 11-60 using a standard NOE-based approach, establishing that it is a very good structural mimic of the folding intermediate of the full-length domain (22). The finding that truncation of the N-terminal residues of the FF domain, and specifically elimination of Thr10 and Trp11, leads to a shift in the monomer-dimer equilibrium toward the monomer form suggests that these residues are responsible for stabilization of the dimer.…”
Section: Resultsmentioning
confidence: 99%
“…The plasmid-encoding FF 1-60 (residues 1-60) was obtained using the QuikChange protocol (Stratagene) by introducing a stop codon after position 60 in the gene encoding the full-length domain cloned into a modified pRSET vector (13). The plasmids for FF domain variants with truncated N termini, FF 7-60 , FF 9-60 , and FF 11-60 , were produced from a plasmid encoding FF 1-60 as described elsewhere (22). All NMR experiments were performed on samples with protein concentrations of approximately 0.3 mM, 50 mM sodium acetate, 100 mM NaCl, pH ¼ 4.9, 25°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation